SCIDOT-24. INCREASING INDUCED NEURAL STEM CELL PERSISTENCE IN THE TUMOR RESECTION CAVITY. (11th November 2019) - Bomba, Hunter; Sheets, Kevin; Carey-Ewend, Abigail; Goetz, Morgan; Bago, Juli; Khagi, Simon; Hingtgen, Shawn
Abstract: Glioblastoma multiforme (GBM) is the most common primary brain cancer in adults. Afflicted patients have a median survival rate of only 15 months, and patient survival statistics have remained stagnant for over three decades. Current standard of care includes maximal safe tumor resection, chemotherapy, and radiation. Nevertheless, GBM is aggressive, making recurrence and deeper tumor infiltration inevitable. Neural stem cells transdifferentiated from a skin biopsy, i.e. induced neural stem cells (iNSCs), have the innate ability to home to tumors, and, when engineered with cytotoxic proteins, can actively kill cancer cells. However, direct injection of these cells into the hostile immune environment of the tumor resection cavity results in an accelerated clearance rate and therefore a shortened therapeutic window. To combat this clearance issue, we investigated the FDA-approved hemostatic matrix, Floseal, as a cell delivery platform to increase iNSC persistence. In vitro, SEM imaging showed homogeneous iNSC distribution throughout Floseal. Using our surgical resection model of GBM in mice, we delivered iNSCs into the post-surgical cavity in Floseal and by direct injection to model current clinical delivery strategies. Serial kinetic imaging showed that human iNSC persistence delivered into the cavity in Floseal persisted over 90 days, while cells directly injected into the brain parenchyma persist less than 20 days. When we investigated the impact on tumor kill, we found the increase in persistence increased survival of GBM-bearing mice more than 30 days compared to control cells. Light-sheet microscopy showed wild-type neural stem cells migrate into invasive GBM-8 tumors in the contralateral hemisphere, and we are now using this approach to validate the homing of iNSCs delivered via Floseal. Administration of iNSCs encapsulated in the biocompatible Floseal matrix offers a promising, clinically-translatable therapeutic strategy for GBM.